Channel revetment steel sheet pile anticorrosive concrete and preparation method thereof
Patent Information
- Application Number
- CN202611122776.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-28
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种航道护岸钢板桩防腐混凝土及其制备方法,解决了航道护岸工程中,热轧U型钢板桩在干湿交替与富氯环境中易发生严重锈蚀,且常规防腐混凝土在光滑钢板桩表面附着力弱、界面易产生泌水通道从而导致防腐体系早期失效与结构承载力下降的问题
1、本发明通过将聚乙烯醇、海藻酸钠、十水合四硼酸钠与硅酸镁锂纳米片复合并配制成分散液替代拌和水,结合浇筑时的高频振捣操作,使混凝土拌合物具备触变特性。在机械振捣时浆体流动性增大,能够紧密贴合钢板桩边界;振捣结束后浆体黏度回升,限制了内部水分向外渗出,减少了钢板桩界面的泌水通道,提高了防腐混凝土在钢板桩表面的附着力。
Smart Images

Figure CN122627749B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials, specifically to a type of anti-corrosion concrete for waterway revetment using steel sheet piles and its preparation method. Background Technology
[0002] In waterway revetment engineering, anti-corrosion concrete is typically poured over the exterior of hot-rolled U-shaped steel sheet piles to extend the structure's service life. However, conventional anti-corrosion concrete still faces some problems in practical applications. Because the surface of hot-rolled steel sheet piles is relatively smooth, after pouring and vibration, moisture in conventional concrete easily migrates outward and accumulates at the joint surfaces of the steel sheet piles, causing localized bleeding. These bleeding channels transform into microscopic defects at the interface after the concrete hardens, reducing the adhesion of the anti-corrosion concrete to the steel surface.
[0003] Meanwhile, the interior of conventional hardened concrete matrix generally contains capillary pores, and the hydration products fail to fill the pores to a deep depth, making it easy for moisture and chloride ions from the external environment to penetrate into the matrix through these physically connected channels, thus limiting the overall impermeability of the structure.
[0004] Furthermore, most existing anti-corrosion concrete relies on a single physical barrier method, lacking a chemical anti-corrosion mechanism at the steel sheet pile interface. Once dissolved oxygen and corrosive media from the external environment penetrate the pores and reach the steel surface, they will react directly with the iron matrix, making it difficult to inhibit the corrosion process of the steel sheet pile in actual service environments. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing anti-corrosion concrete for steel sheet piles used in waterway revetments. This method solves the problems in waterway revetment projects, such as the severe corrosion of hot-rolled U-shaped steel sheet piles in alternating wet and dry environments and chlorine-rich environments, and the weak adhesion of conventional anti-corrosion concrete to smooth steel sheet pile surfaces, which leads to water seepage channels at the interface and thus early failure of the anti-corrosion system and a decrease in structural bearing capacity.
[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a waterway revetment steel sheet pile anti-corrosion concrete, which is made from raw materials including cementitious materials, fine aggregates, coarse aggregates and a composite anti-corrosion dispersion added as mixing water. The raw materials are formulated to meet the following requirements: water-to-binder ratio of 0.35–0.42, bone-to-binder ratio of 2.5–3.5, and sand content of 38.0%–45.0%. The composite anti-corrosion dispersion comprises the following components in parts by weight: 100 samples of industrial tap water; 0.5–1.2 parts of artificially synthesized lithium magnesium silicate nanosheets; 0.5–1.5 parts of partially hydrolyzed polyvinyl alcohol; Sodium alginate powder, 0.1–0.4 parts; Sodium tetraborate decahydrate, 0.05–0.15 parts; Sodium gluconate 0.1–0.3 parts; 3.0–8.0 parts of neutral silica sol; 2.0–5.0 parts of industrial-grade zinc phosphate powder; The cementitious material is composed of 35.0% to 45.0% silicate cement clinker and 55.0% to 65.0% granulated blast furnace slag powder, accounting for 35.0% to 45.0% of the total weight of the cementitious material.
[0007] By adopting the above technical solution, a rheology regulation system is constructed using partially hydrolyzed polyvinyl alcohol, sodium alginate, sodium tetraborate decahydrate, and artificially synthesized lithium magnesium silicate nanosheets. A secondary hydration reaction is initiated between neutral silica sol and high-dosage granulated blast furnace slag powder. Industrial-grade zinc phosphate powder provides chemical passivation. Therefore, an anti-corrosion effect is achieved by improving the interfacial cohesion of concrete slurry on the surface of hot-rolled U-shaped steel sheet piles and effectively inhibiting the corrosion of the sheet piles. The specific reaction mechanism and innovative process are described in the following steps: Step 1: Rheological State Control. In the composite anticorrosive dispersion, sodium tetraborate decahydrate can undergo a cross-linking reaction with partially hydrolyzed polyvinyl alcohol and sodium alginate to form a gel system with a certain consistency. Artificially synthesized lithium magnesium silicate nanosheets further enhance the physical bonding strength of this system. This combination gives the mixture significant thixotropic properties. When the anticorrosive concrete slurry is subjected to high-frequency mechanical vibration, the internal consistency structure of the system is temporarily broken, and the slurry exhibits shear thinning, increasing its fluidity. This allows the slurry to smoothly and tightly encapsulate the hot-rolled U-shaped steel sheet piles. After vibration stops, the viscosity of the slurry recovers quickly, thus limiting excessive migration and seepage of internal moisture and reducing localized bleeding on the surface of the steel sheet piles.
[0008] The second step is hydration and densification. Silicate cement clinker undergoes hydration upon the addition of water, producing calcium hydroxide as a byproduct. The neutral silica sol introduced into the formulation reacts with a large amount of granulated blast furnace slag powder in this alkaline environment, generating hydrated calcium silicate gel with a filling effect. These hydration products extensively fill the internal pores of the hardened concrete, physically blocking the penetration pathway of external chloride ions into the interior. Simultaneously, sodium gluconate is used as a retarder, moderately delaying the early hydration process, allowing the silica sol and slag powder more time to react, ensuring the overall density of the hardened concrete.
[0009] The third step is interfacial chemical corrosion protection. Industrial-grade zinc phosphate powder, uniformly suspended in the concrete system, reacts near the surface of the sheet pile. The zinc and phosphate ions combine with the steel matrix, depositing a layer of iron phosphate double salt passivation and slightly soluble precipitates on the sheet pile surface. These substances adhere to the interface between the sheet pile and the concrete, relatively isolating dissolved oxygen and chloride ions from the iron matrix, thus inhibiting rusting of the sheet pile.
[0010] Preferably, the synthetic magnesium lithium silicate nanosheets have a single-sheet diameter of 25-30 nm and a thickness of 0.8-1.2 nm; the neutral silica sol has an average particle size of 10-20 nm; the industrial-grade zinc phosphate powder has a median particle size of 2.0-5.0 μm; the partially hydrolyzed polyvinyl alcohol has a degree of hydrolysis of 87.0%-89.0% and an average degree of polymerization of 1700-1800; and the sodium alginate powder, when prepared into a 1% (w / w) sodium alginate aqueous solution, has a viscosity of 200-300 mPa·s at 20°C.
[0011] By employing the above technical solution and limiting parameters such as the size, degree of hydrolysis, degree of polymerization, and viscosity of each component, it is possible to ensure that the material maintains good dispersion and dissolution after adding water, while also providing suitable slurry skeleton strength during crosslinking. The specific size range allows the solid particle components to smoothly enter the transition zone on the surface of the sheet pile and participate in the subsequent anti-corrosion precipitation reaction.
[0012] Preferably, the fine aggregate is medium-coarse river sand, and the coarse aggregate is continuously graded crushed stone with a particle size of 5.0-25.0 mm; the cementitious material is composed of silicate cement clinker accounting for 40.0% of the total weight of the cementitious material and granulated blast furnace slag powder accounting for 60.0%; the water-cement ratio is 0.38, the aggregate-cement ratio is 3.0, and the sand ratio is 41.5%.
[0013] By adopting the above technical solutions and limiting the specific gradation and binder ratio of the aggregate, it is beneficial for the aggregate to form a dense packing inside the concrete, reducing shrinkage stress during the matrix hardening process. Limiting the ratio of silicate cement clinker to granulated blast furnace slag powder and the water-binder ratio of 0.38 is to ensure an alkaline activation environment while consuming excess free calcium hydroxide as much as possible, thereby reducing the risk of drying shrinkage cracking in the concrete.
[0014] Secondly, the present invention provides a method for preparing anti-corrosion concrete for waterway revetment using steel sheet piles, comprising the following steps: In a twin-shaft concrete mixer, coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added and dry-mixed to obtain a dry-mixed mixture. The pre-prepared composite anti-corrosion dispersion is added to the twin-shaft concrete mixer and forcibly mixed with the dry mixture to obtain anti-corrosion concrete slurry. The anti-corrosion concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles. The anti-corrosion concrete slurry forms a boundary slurry-rich transition zone on the surface of the hot-rolled U-shaped steel sheet piles. A high-frequency vibrator is inserted into the anti-corrosion concrete slurry in the cast-in-place tie beam formwork. The high-frequency vibrator is turned on to vibrate, and the mechanical vibration generated by the high-frequency vibrator causes shear thinning in the boundary slurry-rich transition zone. After vibration, the high-frequency vibrator is removed to allow the anti-corrosion concrete slurry to undergo a static hydration reaction. Once static hydration is complete and the slurry has hardened, anti-corrosion concrete for waterway revetment steel sheet piles is obtained.
[0015] By adopting the above technical solution, the pre-prepared composite anti-corrosion dispersion is added as mixing water. Furthermore, the mechanical vibration of a high-frequency vibrator induces shear thinning in the boundary slurry-rich transition zone, thus achieving a structural anti-corrosion effect that improves the density of the slurry-sheet pile interface and prevents interfacial bleeding. The specific steps and underlying mechanisms are explained below: Step 1: Homogeneous Mixing. Various corrosion inhibitors are pre-mixed into a liquid state using a composite anti-corrosion dispersion, replacing ordinary mixing water when added to the dry materials. The liquid components more easily wet the surfaces of cement and slag powder, avoiding the localized clumping that easily occurs when traditional powdered corrosion inhibitors are directly added, ensuring uniform distribution of various anti-corrosion components within the concrete system.
[0016] The second step is vibration thinning. After the thixotropic slurry is poured into the mold, it is vibrated using a high-frequency vibrator. The mechanical shear force generated by vibration acts on the rigid boundary of the sheet pile, forcibly breaking the original consistency structure of the slurry. At this time, the slurry in the boundary rich transition zone undergoes shear thinning, its fluidity increases, and it carries the internal components such as silica sol and zinc phosphate towards the surface of the sheet pile along with the slurry, while expelling air bubbles at the interface, forming a relatively tightly bonded rich slurry phase.
[0017] Step 3: Static Curing. After the high-frequency vibrator is removed, the mechanical shear force disappears. The viscosity of the slurry rapidly increases during static curing, preventing water exudation and thus stably retaining the enriched anti-corrosion components on the surface of the sheet pile. During the subsequent static hardening process, the anti-corrosion components continue to undergo hydration and passivation reactions at the interface, eventually hardening and forming a protective layer.
[0018] Preferably, the input is as follows: coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added in sequence; the dry mixing is performed by turning on the twin-shaft concrete mixer and mixing evenly, and the dry mixing time is 15 to 20 seconds.
[0019] While keeping the twin-shaft concrete mixer running, the composite anti-corrosion dispersion is pumped into the twin-shaft concrete mixer in one go using a fluid pump; the forced mixing time is 90-120 seconds, and the material is discharged after forced mixing.
[0020] The anti-corrosion concrete slurry forms a boundary slurry-rich transition zone within a range of 0-5mm from the surface of the hot-rolled U-shaped steel sheet pile; the high-frequency vibrator is inserted at a normal distance of 10-15cm from the surface of the hot-rolled U-shaped steel sheet pile, along a direction parallel to the hot-rolled U-shaped steel sheet pile; the vibration frequency of the high-frequency vibrator is set to 150-200Hz, and the designated point is continuously vibrated for 30-50 seconds.
[0021] The operation of removing the high-frequency vibrator is as follows: it is slowly and uniformly removed at a speed of 0.1 to 0.2 m / s; the static hydration reaction of the anti-corrosion concrete slurry is carried out in a state without mechanical interference.
[0022] By adopting the above technical solution, the feeding sequence and dry mixing time of coarse and fine aggregates and powder are limited, and the powder is initially dispersed by the physical collision of coarse aggregates. Fluid is pumped in at once and the mixing time is controlled to ensure uniform mixing of the slurry and avoid over-mixing that could damage the thixotropic properties of the material. Limiting the insertion distance to 10–15 cm and the high-frequency vibration parameters allows the vibration energy to be better transmitted to the 0–5 mm boundary area to provide local shear force, while also preventing the vibrator from directly damaging the sheet pile. Slow extraction at a speed of 0.1–0.2 m / s prevents excessively rapid extraction from leaving voids or defects inside the concrete.
[0023] Preferably, the preparation process of the pre-prepared composite anticorrosive dispersion includes a pre-stage preparation of an intermediate mixture, which is carried out as follows: industrial tap water is injected into a closed dispersion vessel equipped with a high-shear disperser, a jacketed temperature control device, and a reflux condenser, and the water temperature is adjusted to 35-45°C; the stirrer is turned on, and synthetic magnesium lithium silicate nanosheets are slowly sieved in under low-speed stirring at 500-800 rpm; after the addition is completed, the stirrer speed is increased to 2000-2500 rpm, and high-shear dispersion is continuously carried out for 30-45 min to promote uniform dispersion of synthetic magnesium lithium silicate nanosheets and obtain a primary dispersion. A heat-conducting medium is introduced into the jacket of a sealed dispersion vessel to raise the temperature of the primary dispersion in the vessel to 80–85°C. The stirring speed is then reduced to 500–800 rpm, and a portion of the alcoholysis-type polyvinyl alcohol and sodium alginate powder are slowly added. The mixture is stirred continuously at a constant temperature for 45–60 minutes until the alcoholysis-type polyvinyl alcohol and sodium alginate powder dissolve, thus obtaining an intermediate mixture.
[0024] It also includes the stage of finally obtaining the composite anticorrosive dispersion from the intermediate mixture. The operation is as follows: cooling water is introduced into the jacket of the closed dispersion vessel to cool the intermediate mixture in the closed dispersion vessel to 55-60°C; sodium tetraborate decahydrate and sodium gluconate are added to the closed dispersion vessel, the stirring speed is reduced to 300-500 rpm, and the reaction is carried out at a constant temperature for 20-30 minutes to obtain the crosslinked mixture. The cross-linked mixture in the sealed dispersion vessel is further cooled to 35-40°C, and neutral silica sol is added dropwise at a uniform rate. The mixture is stirred for 10-15 minutes to obtain a silica-containing mixture. Industrial-grade zinc phosphate powder is added to the silica-containing mixture, and the stirring speed is increased to 1000-1500 rpm. The mixture is continuously dispersed for 20-30 minutes to promote the mixing of the silica-containing mixture and the industrial-grade zinc phosphate powder into a uniformly suspended composite anti-corrosion dispersion. The mixture is then discharged for later use.
[0025] The above-mentioned technical solution, which involves multi-stage temperature control and variable speed preparation, is adopted because the dispersion and dissolution of different materials require different physical environments. Initially, lithium magnesium silicate nanosheets are forcibly dispersed at 35–45°C and a relatively high rotation speed. Then, the temperature is raised to 80–85°C to help polyvinyl alcohol and sodium alginate completely dissolve without clumping. The temperature is lowered to 55–60°C to add sodium tetraborate decahydrate, which controls the overall speed of the cross-linking reaction and prevents the formation of unstirrable gel clumps due to excessively rapid reaction. The temperature is further lowered to 35–40°C to add neutral silica sol dropwise, preventing thermal coagulation caused by high temperatures. Finally, zinc phosphate powder is mixed in at a specific rotation speed, relying on the previously formed dispersion system with a certain consistency to prevent the sedimentation of denser powders, ultimately resulting in a stable suspension.
[0026] This invention provides a corrosion-resistant concrete for waterway revetment using steel sheet piles and its preparation method. It has the following beneficial effects: 1. This invention uses a dispersion made of polyvinyl alcohol, sodium alginate, sodium tetraborate decahydrate, and lithium magnesium silicate nanosheets to replace mixing water. Combined with high-frequency vibration during pouring, this imparts thixotropic properties to the concrete mixture. During mechanical vibration, the fluidity of the slurry increases, allowing it to adhere tightly to the steel sheet pile boundary. After vibration, the slurry viscosity returns to normal, limiting the outward seepage of internal moisture, reducing bleeding channels at the steel sheet pile interface, and improving the adhesion of the anti-corrosion concrete to the steel sheet pile surface.
[0027] 2. This invention employs a component design that combines neutral silica sol, granulated blast furnace slag powder, and silicate cement clinker. By utilizing the alkaline environment generated during the initial hydration of cement, the silica sol and slag powder react, producing a hydration gel that fills the internal pores of hardened concrete. This reduces the overall porosity of the concrete, cuts off the physical pathways for external chloride ions and moisture to penetrate into the matrix, and enhances the impermeability of the concrete structure.
[0028] 3. This invention introduces zinc phosphate powder into the raw materials and utilizes the slurry-rich transition zone formed by the thixotropic coating in the early stage to promote the zinc ions and phosphate ions released by zinc phosphate to concentrate at the interface of the steel sheet pile and react to deposit a passivating substance on the steel surface. The deposit acts as an isolation layer, which prevents the direct contact between dissolved oxygen and the iron matrix, thereby inhibiting the corrosion process of the steel sheet pile in the service environment. Attached Figure Description
[0029] Figure 1 The apparent viscosity versus logarithmic shear rate curves are used to test the rheological response performance of the composite anti-corrosion dispersion of the present invention. Figure 2 This is a line graph showing the evolution of the compressive strength of the anti-corrosion concrete for waterway revetment as a function of age. Figure 3 This is a graph showing the tensile displacement and stress curves during the normal drawing process of the interface micro-region of the present invention. Figure 4 The Nyquist plot of the AC impedance spectrum is used for testing the electrochemical corrosion resistance of this invention. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] Preparation Examples 1-3: Preparation Example 1: This preparation example provides a composite anti-corrosion dispersion for anti-corrosion concrete made from steel sheet piles for waterway revetment, comprising the following steps: By weight, 100 parts of industrial tap water were injected into a sealed dispersion vessel equipped with a high-shear disperser, a jacketed temperature control device, and a reflux condenser, and the water temperature was adjusted to 35°C. The stirrer was turned on, and 0.5 parts of synthetically produced lithium magnesium silicate nanosheets (each with a diameter of 25 nm and a thickness of 0.8 nm) were slowly sieved in at a low stirring speed of 500 rpm. After the addition was complete, the stirrer speed was increased to 2000 rpm, and continuous high-shear dispersion was performed for 30 minutes to ensure uniform dispersion of the synthetically produced lithium magnesium silicate nanosheets, thus obtaining a primary dispersion.
[0032] A heat-conducting medium was introduced into the jacket of the dispersion vessel to raise the temperature of the primary dispersion to 80°C. The stirrer speed was reduced to 500 rpm, and 0.5 parts of partially hydrolyzed polyvinyl alcohol (degree of hydrolysis 87.0%, average degree of polymerization 1700) and 0.1 parts of sodium alginate powder (a 1% sodium alginate aqueous solution has a viscosity of 200 mPa·s at 20°C) were slowly added. The mixture was stirred continuously at a constant temperature for 45 min until the partially hydrolyzed polyvinyl alcohol and sodium alginate powder dissolved, yielding an intermediate mixture.
[0033] Cooling water was circulated into the jacket of the dispersion vessel to lower the temperature of the intermediate mixture to 55°C. 0.05 parts of sodium tetraborate decahydrate and 0.1 parts of sodium gluconate were added to the dispersion vessel, and the stirrer speed was reduced to 300 rpm. The mixture was reacted at a constant temperature for 20 minutes to obtain a crosslinked mixture. The crosslinked mixture in the dispersion vessel was further cooled to 35°C, and 3.0 parts of neutral silica sol (average particle size of 10 nm) were added dropwise at a uniform rate. The mixture was then stirred for 10 minutes to obtain a silica-containing mixture.
[0034] Add 2.0 parts of industrial-grade zinc phosphate powder (median particle size of 2.0 μm) to the silicon-containing mixture, increase the stirring speed to 1000 rpm, and continue to disperse for 20 minutes to make the silicon-containing mixture and zinc phosphate powder a uniformly suspended composite anti-corrosion dispersion. Discharge the material for later use.
[0035] Preparation Example 2: This preparation example provides a composite anti-corrosion dispersion for anti-corrosion concrete made from steel sheet piles for waterway revetment, comprising the following steps: By weight, 100 parts of industrial tap water were injected into a sealed dispersion vessel equipped with a high-shear disperser, a jacketed temperature control device, and a reflux condenser, and the water temperature was adjusted to 40°C. The stirrer was turned on, and 0.85 parts of synthetically produced lithium magnesium silicate nanosheets (each with a diameter of 27 nm and a thickness of 1.0 nm) were slowly sieved in at a low stirring speed of 650 rpm. After the addition was complete, the stirrer speed was increased to 2250 rpm, and continuous high-shear dispersion was performed for 37 minutes to ensure uniform dispersion of the synthetically produced lithium magnesium silicate nanosheets, thus obtaining a primary dispersion.
[0036] A heat transfer medium was introduced into the jacket of the dispersion vessel to raise the temperature of the primary dispersion to 82°C. The stirrer speed was reduced to 650 rpm, and 1.0 part of partially hydrolyzed polyvinyl alcohol (degree of hydrolysis 88.0%, average degree of polymerization 1750) and 0.25 parts of sodium alginate powder (a 1% sodium alginate aqueous solution has a viscosity of 250 mPa·s at 20°C) were slowly added. The set temperature was maintained and the mixture was stirred continuously for 52 min until the partially hydrolyzed polyvinyl alcohol and sodium alginate powder dissolved, yielding an intermediate mixture.
[0037] Cooling water was circulated into the jacket of the dispersion vessel to lower the temperature of the intermediate mixture to 57°C. 0.10 parts of sodium tetraborate decahydrate and 0.2 parts of sodium gluconate were added to the dispersion vessel, and the stirrer speed was reduced to 400 rpm. The mixture was reacted at a constant temperature for 25 minutes to obtain a crosslinked mixture. The crosslinked mixture in the dispersion vessel was further cooled to 37°C, and 5.5 parts of neutral silica sol (average particle size of 15 nm) were added dropwise at a uniform rate. The mixture was then stirred for 12 minutes to obtain a silica-containing mixture.
[0038] Add 3.5 parts of industrial-grade zinc phosphate powder (median particle size of 3.5 μm) to the silicon-containing mixture, increase the stirring speed to 1250 rpm, and continue to disperse for 25 min to make the silicon-containing mixture and zinc phosphate powder a uniformly suspended composite anti-corrosion dispersion. Discharge the material for later use.
[0039] Preparation Example 3: This preparation example provides a composite anti-corrosion dispersion for anti-corrosion concrete made from steel sheet piles for waterway revetment, comprising the following steps: By weight, 100 parts of industrial tap water were injected into a sealed dispersion vessel equipped with a high-shear disperser, a jacketed temperature control device, and a reflux condenser, and the water temperature was adjusted to 45°C. The stirrer was turned on, and 1.2 parts of synthetically produced lithium magnesium silicate nanosheets (each 30 nm in diameter and 1.2 nm in thickness) were slowly sieved in at a low stirring speed of 800 rpm. After the addition was complete, the stirrer speed was increased to 2500 rpm, and continuous high-shear dispersion was performed for 45 minutes to ensure uniform dispersion of the synthetically produced lithium magnesium silicate nanosheets, thus obtaining a primary dispersion.
[0040] A heat transfer medium was introduced into the jacket of the dispersion vessel to raise the temperature of the primary dispersion to 85°C. The stirrer speed was reduced to 800 rpm, and 1.5 parts of partially hydrolyzed polyvinyl alcohol (degree of hydrolysis 89.0%, average degree of polymerization 1800) and 0.4 parts of sodium alginate powder (a 1% sodium alginate aqueous solution with a viscosity of 300 mPa·s at 20°C) were slowly added. The mixture was stirred continuously at the current temperature for 60 minutes until the partially hydrolyzed polyvinyl alcohol and sodium alginate powder dissolved, yielding an intermediate mixture.
[0041] Cooling water was circulated into the jacket of the dispersion vessel to lower the temperature of the intermediate mixture to 60°C. 0.15 parts of sodium tetraborate decahydrate and 0.3 parts of sodium gluconate were added to the dispersion vessel, and the stirrer speed was reduced to 500 rpm. The reaction was carried out at a constant temperature for 30 minutes to obtain a crosslinked mixture. The crosslinked mixture in the dispersion vessel was further cooled to 40°C, and 8.0 parts of neutral silica sol (average particle size of 20 nm) were added dropwise at a uniform rate. The mixture was stirred for 15 minutes to obtain a silica-containing mixture.
[0042] Add 5.0 parts of industrial-grade zinc phosphate powder (median particle size of 5.0 μm) to the silicon-containing mixture, increase the stirring speed to 1500 rpm, and continue to disperse for 30 min to make the silicon-containing mixture and zinc phosphate powder a uniformly suspended composite anti-corrosion dispersion. Discharge the material for later use.
[0043] Examples 1-3: Example 1: This embodiment provides a method for preparing anti-corrosion concrete for waterway revetment using steel sheet piles, including the following steps: Based on the percentage of total weight of cementitious materials, 35.0% of silicate cement clinker and 65.0% of granulated blast furnace slag powder were weighed as cementitious materials. The total amount of mixing water was calculated according to a water-cement ratio of 0.35. The calculated total amount of mixing water was proportionally converted to 100 parts of industrial tap water in Preparation Example 1, and the addition amount of the remaining components was calculated according to the weight proportions in Preparation Example 1 to pre-prepare the composite anti-corrosion dispersion in Preparation Example 1. Fine aggregate and coarse aggregate were weighed according to a bone-cement ratio of 2.5 and a sand ratio of 38.0%. Medium-coarse river sand was used as fine aggregate, and continuously graded crushed stone with a particle size of 5.0–25.0 mm was used as coarse aggregate.
[0044] In a twin-shaft concrete mixer, the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added in sequence. The twin-shaft concrete mixer is then turned on and dry-mixed for 15 seconds to ensure that the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are mixed evenly to obtain a dry-mixed mixture.
[0045] After dry mixing is completed, the twin-shaft concrete mixer is kept running, and the pre-prepared composite anti-corrosion dispersion is pumped into the twin-shaft concrete mixer in one go through a fluid pump to mix with the dry mixture. Forced mixing is maintained for 90 seconds, and the material is discharged to obtain anti-corrosion concrete slurry.
[0046] Anticorrosive concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles. A boundary rich slurry transition zone is formed within a 0-5mm range from the surface of the hot-rolled U-shaped steel sheet piles. At a normal distance of 10cm from the surface of the hot-rolled U-shaped steel sheet piles, a high-frequency vibrator is inserted into the anticorrosive concrete slurry within the cast-in-place tie beam formwork, parallel to the direction of the hot-rolled U-shaped steel sheet piles. Vibration is performed by turning on the high-frequency vibrator, and the mechanical vibration generated by the vibrator causes shear thinning in the boundary rich slurry transition zone. The vibration frequency of the high-frequency vibrator is set to 150Hz, and single-point vibration is performed continuously for 30 seconds at a designated location. After vibration, the high-frequency vibrator is slowly and uniformly withdrawn at a speed of 0.1m / s. The anticorrosive concrete slurry is then allowed to undergo a static hydration reaction without mechanical interference. After static hydration is complete and the slurry has hardened, the anticorrosive concrete for the waterway revetment steel sheet piles is obtained.
[0047] Example 2: This embodiment provides a method for preparing anti-corrosion concrete for waterway revetment using steel sheet piles, including the following steps: Based on the percentage of total weight of cementitious materials, 40.0% of silicate cement clinker and 60.0% of granulated blast furnace slag powder were weighed as cementitious materials. The total amount of mixing water was calculated according to a water-cement ratio of 0.38. The calculated total amount of mixing water was proportionally converted to 100 parts of industrial tap water in Preparation Example 2, and the addition amount of the remaining components was calculated according to the weight proportions in Preparation Example 2 to pre-prepare the composite anti-corrosion dispersion in Preparation Example 2. Fine aggregate and coarse aggregate were weighed according to a bone-cement ratio of 3.0 and a sand ratio of 41.5%. The fine aggregate was medium-coarse river sand, and the coarse aggregate was continuously graded crushed stone with a particle size of 5.0–25.0 mm.
[0048] In a twin-shaft concrete mixer, the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added in sequence. The twin-shaft concrete mixer is then turned on and dry-mixed for 18 seconds to ensure that the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are mixed evenly to obtain a dry-mixed mixture.
[0049] After dry mixing, keep the twin-shaft concrete mixer running and pump the pre-prepared composite anti-corrosion dispersion into the twin-shaft concrete mixer in one go through the fluid pump. Mix it with the dry mixture and maintain forced mixing for 105 seconds. Then discharge the material to obtain anti-corrosion concrete slurry.
[0050] Anticorrosive concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles. A boundary rich slurry transition zone is formed within 0-5mm of the hot-rolled U-shaped steel sheet pile surface. At a distance of 12.5cm normal to the surface of the hot-rolled U-shaped steel sheet pile, a high-frequency vibrator is inserted into the anticorrosive concrete slurry within the cast-in-place tie beam formwork, parallel to the direction of the hot-rolled U-shaped steel sheet pile. Vibration is performed by turning on the high-frequency vibrator, and the mechanical vibration generated by the vibrator causes shear thinning in the boundary rich slurry transition zone. The vibration frequency of the high-frequency vibrator is set to 175Hz, and single-point vibration is performed continuously for 40 seconds at a designated location. After vibration, the high-frequency vibrator is slowly and uniformly withdrawn at a speed of 0.15m / s. The anticorrosive concrete slurry is then allowed to undergo a static hydration reaction without mechanical interference. After static hydration is complete and the slurry hardens, the anticorrosive concrete for the waterway revetment steel sheet piles is obtained.
[0051] Example 3: This embodiment provides a method for preparing anti-corrosion concrete for waterway revetment using steel sheet piles, including the following steps: Based on the percentage of total weight of cementitious materials, 45.0% of silicate cement clinker and 55.0% of granulated blast furnace slag powder were weighed as cementitious materials. The total amount of mixing water was calculated according to a water-cement ratio of 0.42. The calculated total amount of mixing water was proportionally converted to 100 parts of industrial tap water in Preparation Example 3, and the addition amount of the remaining components was calculated according to the weight proportions in Preparation Example 3 to pre-prepare the composite anti-corrosion dispersion in Preparation Example 3. Fine aggregate and coarse aggregate were weighed according to a bone-cement ratio of 3.5 and a sand ratio of 45.0%. Medium-coarse river sand was used as fine aggregate, and continuously graded crushed stone with a particle size of 5.0–25.0 mm was used as coarse aggregate.
[0052] In a twin-shaft concrete mixer, the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added in sequence. The twin-shaft concrete mixer is then turned on and dry-mixed for 20 seconds to ensure that the weighed coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are mixed evenly to obtain a dry-mixed mixture.
[0053] After dry mixing is completed, the twin-shaft concrete mixer is kept running, and the pre-prepared composite anti-corrosion dispersion is pumped into the twin-shaft concrete mixer in one go through a fluid pump to mix with the dry mixture. Forced mixing is maintained for 120 seconds, and the material is discharged to obtain anti-corrosion concrete slurry.
[0054] Anticorrosive concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles. A boundary rich slurry transition zone is formed within 0-5mm of the hot-rolled U-shaped steel sheet pile surface. A high-frequency vibrator is inserted into the anticorrosive concrete slurry within the cast-in-place tie beam formwork at a normal distance of 15cm from the surface of the hot-rolled U-shaped steel sheet piles, parallel to the direction of the hot-rolled U-shaped steel sheet piles. Vibration is performed by turning on the high-frequency vibrator, and the mechanical vibration generated by the vibrator causes shear thinning in the boundary rich slurry transition zone. The vibration frequency of the high-frequency vibrator is set to 200Hz, and single-point vibration is performed continuously for 50 seconds at a designated location. After vibration, the high-frequency vibrator is slowly and uniformly withdrawn at a speed of 0.2m / s. The anticorrosive concrete slurry is then allowed to undergo a static hydration reaction without mechanical interference. After static hydration is complete and the slurry hardens, the anticorrosive concrete for the waterway revetment steel sheet piles is obtained.
[0055] Comparative Examples 1-7: Comparative Example 1: Compared with Example 2, the difference is that no composite anti-corrosion dispersion was added. Instead, an equal amount of industrial tap water was used instead of the composite anti-corrosion dispersion in the twin-shaft concrete mixer. All other aspects are the same.
[0056] Comparative Example 2: The difference from Example 2 is that no artificially synthesized lithium magnesium silicate nanosheets were added when preparing the composite anticorrosive dispersion; all other aspects are the same.
[0057] Comparative Example 3: The difference from Example 2 is that sodium alginate powder was not added when preparing the composite preservative dispersion; all other aspects are the same.
[0058] Comparative Example 4: Compared with Example 2, the difference is that a high-frequency vibrator is inserted into the anti-corrosion concrete slurry inside the cast-in-place tie beam formwork at a normal distance of 0cm from the surface of the hot-rolled U-shaped steel sheet pile, that is, close to the surface of the hot-rolled U-shaped steel sheet pile. All other aspects are the same.
[0059] Comparative Example 5: Compared with Example 2, the difference is that the composite anti-corrosion dispersion was not prepared in advance through a dispersion tank. Instead, the various raw material components contained in the composite anti-corrosion dispersion were directly added to the twin-shaft concrete mixer along with the mixing water according to the original formula ratio for mixing. All other aspects are the same.
[0060] Comparative Example 6: The difference from Example 2 is that neutral silica sol was not added when preparing the composite anticorrosive dispersion; all other aspects are the same.
[0061] Comparative Example 7: The difference from Example 2 is that no industrial-grade zinc phosphate powder was added when preparing the composite anticorrosive dispersion; all other aspects are the same.
[0062] Test Examples 1-4: Test Example 1: The composite anticorrosive dispersions prepared in Examples 1 to 3 were selected as rheological test samples. The rheological test samples were injected into the coaxial cylindrical measurement module of a rotational rheometer, and the measurement system temperature was set to 25°C, with a static temperature hold time of 5 minutes. The instrument shear rate was controlled from 0.1 s⁻¹. -1 Scan to 100s -1 The apparent viscosity within the scanned range was recorded. The shear rate was extracted at 0.1 s⁻¹. -1 The low shear apparent viscosity and shear rate at 100 s⁻¹ -1 The apparent viscosity at high shear is used to calculate the apparent viscosity drop rate.
[0063] 50 mL of the composite anticorrosive dispersions prepared in Examples 1, 2, and 3 were measured as phase change test samples and placed in glass beakers for magnetic stirring at 200 rpm. A 10 mL saturated calcium hydroxide solution was then rapidly injected into the glass beakers to simulate the reaction environment of calcium-rich pore liquid generated during cement hydration. The fluid state was monitored using a resistance sensor, and the time it took for the magnetic stirring rotor to stop due to loss of fluidity within the system was defined as the gelation time.
[0064] The solid hydrogel product formed in the glass beaker was removed and rinsed three times with deionized water to remove residual impurities. The rinsed solid hydrogel product was placed in a vacuum drying oven and dried at a constant temperature of 60°C until constant weight. The mass of the dried solid product was weighed and, combined with the theoretical dry weight of sodium alginate and polymer components in the original phase change test sample, the mass retention rate of the insoluble gel was calculated.
[0065] Table 1. Test results of rheological properties and gelation parameters of the composite anticorrosive dispersion Test conclusion: According to Table 1 and Figure 1 The test results showed that the composite antiseptic dispersions prepared in Examples 1, 2, and 3 exhibited a corrosion rate of 0.1 s. -1 A relatively high apparent viscosity was measured within the low shear rate test range. Combined with... Figure 1 The curve trend shows that as the shear rate applied by the rotational rheometer increases to 100 s⁻¹, -1 The apparent viscosity of all three test subjects decreased, and the calculated apparent viscosity drop rate was in the range of 97.25% to 97.41%.
[0066] The viscosity under static, undisturbed conditions reflects the presence of a network support structure within the liquid phase, constructed from interconnected synthetic lithium magnesium silicate nanosheets. This structural state provides the yield stress to resist the sedimentation and separation of solid particles. The decrease in viscosity upon the introduction of shear forces verifies the rheological mechanism by which mechanical shear force causes the destruction of the network support structure. The reduction in fluid viscous resistance indicates that the system possesses the conditions to expel air bubbles and wet the substrate surface.
[0067] During the injection process using a saturated calcium hydroxide solution, the test subject lost its flowability and transformed into a solid hydrogel within a range of 1.31 to 2.46 seconds. The insoluble gel mass retention rate of the resulting solid hydrogel product reached 88.13% to 94.87%. Free calcium ions initiated a coordination cross-linking reaction of the components within the dispersion, verifying the principle that sodium alginate molecular chains undergo cross-linking and solidification reactions to form hydrogels under calcium conditions. The product retained its solid form during rinsing, confirming that the spatial network formed by in-situ cross-linking has a water-retention effect.
[0068] Test Example 2: The anti-corrosion concrete slurry obtained from the output of the twin-shaft concrete mixer in Examples 1 to 3 were selected as the workability test objects. A wetted standard slump cone was placed on the test platform, and the anti-corrosion concrete slurry was poured into the cone in three layers, each layer being compacted with a tamping rod. After smoothing the surface, the slump cone was vertically and steadily pulled out. After the anti-corrosion concrete slurry stopped deforming, the height difference between the cone height and the highest point of the slurry was measured as the initial slump. Simultaneously, the maximum diameter of the slurry in two vertical directions was measured using a steel ruler, and the average value was taken as the spread.
[0069] The remaining anti-corrosion concrete slurry was used as the test material for mechanical properties. The slurry was poured into standardized cast iron molds measuring 150mm × 150mm × 150mm in two batches, placed on a vibrating table, and vibrated to remove air and ensure compaction. Excess slurry was scraped off and smoothed. After standing at room temperature for 24 hours, the molds were removed to obtain hardened anti-corrosion concrete test blocks.
[0070] After demolding, the anti-corrosion concrete test blocks were transferred to a standard curing room with a temperature controlled at 20±2℃ and a relative humidity of not less than 95% for hydration curing. Test blocks from the corresponding batches were removed after 3, 7, and 28 days of curing. The surface moisture of the test blocks was wiped dry, and they were placed on a computer-controlled electro-hydraulic servo universal testing machine. Axial pressure was applied to the test blocks at a constant loading rate until failure occurred. The maximum failure load was recorded, and the compressive strength at the corresponding age was calculated based on the compressed area.
[0071] Table 2. Test results of workability and compressive strength of anti-corrosion concrete for waterway revetments Test conclusion: According to the test results in Table 2, the initial slump of the anti-corrosion concrete slurry prepared in Examples 1, 2, and 3 after discharge ranged from 198 mm to 214 mm, and the spread ranged from 495 mm to 541 mm. The workability parameters indicate that although a composite anti-corrosion dispersion was pre-mixed into the system, the anti-corrosion concrete slurry as a whole maintained its fluidity and lateral extensibility, and no premature setting or water loss occurred. This meets the basic engineering requirements for fluid states in underwater casting or pumping construction.
[0072] Combination Figure 2As shown in the curve trend and the data in Table 2, the compressive strength of the anti-corrosion concrete specimens formed in Examples 1 to 3 increased with the extension of the curing period. At 3 days, the compressive strength of each group of specimens reached 21.4 MPa to 25.1 MPa, demonstrating early load-bearing capacity. After 28 days of hydration, the compressive strength increased to the range of 45.2 MPa to 51.3 MPa. The steady development of compressive strength indicates that the specific chemical components in the composite anti-corrosion dispersion did not adversely affect the normal hydration process of the silicate cement clinker and granulated blast furnace slag powder in the matrix material.
[0073] The strength test results demonstrate that the cementitious materials, including silicate cement clinker and granulated blast furnace slag powder, and the load-bearing framework, including coarse and fine aggregates, can harden and form under predetermined water-cement ratio and sand ratio conditions. The compressive strength meets the mechanical load standards for protective concrete in the channel revetment structure, proving the compatibility of the anti-corrosion chemical system with bulk civil engineering materials at the basic service level.
[0074] Test Example 3: Freshly mixed anti-corrosion concrete slurries prepared from the outputs of Examples 1, 2, 3, Comparative Examples 1, 2, 3, and 4 were weighed respectively. The freshly mixed anti-corrosion concrete slurries were respectively placed into standard measuring cylinders with volume markings, sealed, and allowed to stand for 2 hours. The free water that precipitated from the surface of the measuring cylinders was sucked out using a pipette, the mass of the free water was weighed, and the percentage of the free water mass to the total mass of the mixing water used in the mix was calculated and recorded as the bleeding rate.
[0075] The standard volumetric cylinder containing the freshly mixed anti-corrosion concrete slurry was allowed to stand for another 24 hours. The vertical displacement difference between the top surface of the freshly mixed anti-corrosion concrete slurry and the initial pouring height was measured using vernier calipers and recorded as the vertical settlement.
[0076] Corrosion-resistant concrete specimens containing hot-rolled U-shaped steel sheet piles, cast in Examples 1 to 3 and Comparative Examples 1 to 4, were cured for 28 days under standard conditions at a temperature of 20±2℃ and a relative humidity of 95%. At the interface of the hot-rolled U-shaped steel sheet piles on the surface of the corrosion-resistant concrete specimens, a 15mm deep annular cutting groove was drilled using a hollow core drill bit with cooling water circulation. The annular cutting groove divided the interface area into cylindrical test surfaces.
[0077] High-strength epoxy resin adhesive was applied to the cylindrical test surface, and a metal pull-out head with a matching diameter was pressed and attached. After 24 hours of standing to allow the epoxy resin to fully cure, the metal pull-out head was connected to a digital adhesion pull-out tester. The pull-out tester was controlled to apply a normal pull-out force perpendicular to the surface of the hot-rolled U-shaped steel sheet pile at a constant loading rate of 0.05 MPa / s. The maximum failure load of the metal pull-out head detaching from the interface was recorded, the normal pull-out fracture strength was calculated, and the tensile displacement and stress response parameters throughout the entire pull-out loading process were simultaneously recorded by the connected data acquisition terminal.
[0078] Table 3. Results of interfacial fluid stability and macroscopic normal pull-out strength tests Test conclusion: Combination Figure 3 The stress-displacement curves and data in Table 3 show that the bleeding rate of the anti-corrosion concrete slurry in Examples 1 to 3, measured under static conditions, ranged from 0.43% to 0.81%, and the vertical settlement ranged from 1.18 mm to 2.14 mm. In Comparative Example 2, no synthetic lithium magnesium silicate nanosheets were added during preparation, and the vertical settlement of the anti-corrosion concrete slurry in Comparative Example 2 increased to 12.35 mm. The increase in settlement data indicates that the synthetic lithium magnesium silicate nanosheets provided physical support to the slurry's interior against the gravity-induced settling of solid particles. In Comparative Example 3, no sodium alginate was added during preparation, and the bleeding rate of the anti-corrosion concrete slurry in Comparative Example 3 increased to 5.62%. The increase in free water content verifies that the hydrogel product generated by the cross-linking reaction of sodium alginate in an alkaline hydration environment has a macroscopic physical retention effect on water seepage channels.
[0079] The normal pull-out fracture strength of Examples 1 to 3 ranged from 3.45 MPa to 4.15 MPa. (Combined with...) Figure 3 The stress-displacement curves show that in Example 2, the red solid line indicates that interfacial separation fracture only occurred after reaching a stress peak of 3.82 MPa, demonstrating high interfacial bond strength. Comparative Example 1, which did not use the composite anti-corrosion dispersion, showed a decrease in normal pull-out strength to 1.85 MPa. Figure 3 The blue dashed line indicates a lower peak stress and smaller displacement extension. The difference in stress data confirms that the composite anti-corrosion dispersion improves the physical bonding between the anti-corrosion concrete matrix and the surface of the hot-rolled U-shaped steel sheet pile.
[0080] Comparative Example 4 altered the insertion position of the high-frequency vibrator during the pouring process, ensuring the vibrator was in close contact with the surface of the hot-rolled U-shaped steel sheet pile for vibration. The normal pull-out fracture strength of Comparative Example 4 was only 1.45 MPa, the lowest among all tested samples. Figure 3The black dotted line in Comparative Example 4 reaches its peak value and exhibits a tendency to deteriorate and detach under relatively low stress. The degradation of mechanical properties reflects that mechanical disturbance close to the surface destroys the slurry-rich layer formed within 0 to 5 mm of the sheet pile surface. The test results of the comparative example indicate that the process of applying mechanical force intervention at a set normal distance preserves the slurry-rich layer at the interface. Mechanical vibration promotes the degassing of the enriched layer and interface wetting, forming the basis for improved interface adhesion.
[0081] Test Example 4: Corrosion-resistant concrete specimens containing hot-rolled U-shaped steel sheet piles from Examples 1 to 3, Comparative Examples 1, 5, 6, and 7, were selected and cured for 28 days under standard conditions of 20±2℃ and 95% relative humidity. The corrosion-resistant concrete was cut along a direction parallel to the surface of the hot-rolled U-shaped steel sheet piles, and concrete slices with a thickness of 0 to 5 mm from the steel sheet pile interface were taken as permeability test samples. The permeability test samples were placed in a vacuum water-saturation tank for vacuum saturation treatment.
[0082] The saturated impermeability test sample was installed in the rubber sleeve of the RCM chloride ion migration tester. A 10% sodium chloride solution was injected into the cathode test cell, and a 0.3 mol / L sodium hydroxide solution was injected into the anode test cell. The tester was powered on, and a 30V DC voltage was applied to both ends of the sample for 24 hours. After power was turned off, the impermeability test sample was split axially, and a 0.1 mol / L silver nitrate solution was sprayed onto the split surface. The depth of the colorimetric reaction boundary line on the cross-section was measured using vernier calipers. Based on the temperature and voltage data recorded by the tester, the chloride ion migration coefficient of the test object was calculated.
[0083] Separately, a cured anti-corrosion concrete specimen containing hot-rolled U-shaped steel sheet piles was immersed in a 3.5% sodium chloride solution for 90 days for corrosion treatment. The immersed specimen was then connected to an electrochemical workstation to construct a three-electrode testing system, with the hot-rolled U-shaped steel sheet pile as the working electrode, a saturated calomel electrode as the reference electrode, and a platinum sheet as the auxiliary electrode. After the open-circuit potential of the working electrode stabilized, a sinusoidal AC perturbation voltage of 10mV was applied, controlling the scanning frequency range to decrease from 100kHz to 10mHz. Electrochemical impedance data for the corresponding frequency range were recorded, and the real impedance value corresponding to the extremely low frequency band of 10mHz was extracted as the low-frequency polarization resistance.
[0084] Table 4. Results of interfacial resistance to chloride ion attack and electrochemical polarization resistance tests Test conclusion: According to the data in Table 4, the measured chloride ion migration coefficient at the interface of the anti-corrosion concrete in Examples 1 to 3 was 1.21 × 10⁻⁶. -12 m 2 / s to 1.83×10 -12 m 2 / s. In Comparative Example 1, without the use of the composite anti-corrosion dispersion, the chloride ion migration coefficient increased to 6.75 × 10⁻⁶. -12 m 2 / s. Comparative Example 6 removed the silica sol component during the preparation of the preservative solution, and the chloride ion migration coefficient was 4.92 × 10⁻⁶. -12 m 2 / s. The difference in migration data between Comparative Example 6 and the Example demonstrates that the silica component reduces the diffusion rate of corrosive media in the concrete transition layer and improves the impermeability of the anti-corrosion concrete interface.
[0085] Combination Figure 4 As can be seen from the impedance spectrum capacitive arc radius characteristics and the values in Table 4, the low-frequency polarization resistance of Examples 1 to 3 reached 152.4 kΩ·cm. 2 Up to 214.5 kΩ·cm 2 In the main Nyquist plot, which includes both real and imaginary impedances, the red solid line marked with a circle in Example 3 shows a larger capacitive arc radius. The low-frequency polarization resistance of Comparative Example 1 is only 12.8 kΩ·cm. 2 ,exist Figure 4 In the magnified sub-image, the radius of the capacitive arc marked with a square (blue dashed line) shrinks to the low impedance range. The increase in impedance value verifies that the composite anti-corrosion dispersion has constructed an insulating layer with electrochemical protection on the surface of the hot-rolled U-shaped steel sheet pile.
[0086] Comparative Example 5 used a direct dry-mixing powder method instead of the in-situ pre-dispersion gelation process, resulting in a low-frequency polarization resistance of 45.6 kΩ·cm. 2 Direct dry mixing resulted in uneven dispersion of the anti-corrosion components, creating weak areas in the protective layer deposited at the steel interface. Comparative Example 7, by removing zinc phosphate from its formulation, maintained a chloride ion migration coefficient of 1.68 × 10⁻⁶. -12 m 2 The low-frequency polarization resistance is at the level of / s, but drops to 18.5kΩ·cm. 2 ,exist Figure 4 In the magnified sub-image, the capacitive arc is represented by a contracted black dotted line with a triangular marker. The test data from Comparative Example 7 demonstrate that the introduction of the inorganic zinc source component is a condition for improving the interfacial electrochemical polarization resistance.
Claims
1. A type of anti-corrosion concrete using steel sheet piles for waterway revetment, characterized in that, It is made from raw materials including cementitious materials, fine aggregates, coarse aggregates, and a composite anti-corrosion dispersion added as mixing water; The raw materials are formulated to meet the following requirements: water-to-binder ratio of 0.35–0.42, bone-to-binder ratio of 2.5–3.5, and sand content of 38.0%–45.0%. The composite anti-corrosion dispersion comprises the following components in parts by weight: 100 samples of industrial tap water; 0.5–1.2 parts of artificially synthesized lithium magnesium silicate nanosheets; 0.5–1.5 parts of partially hydrolyzed polyvinyl alcohol; Sodium alginate powder, 0.1–0.4 parts; Sodium tetraborate decahydrate, 0.05–0.15 parts; Sodium gluconate 0.1–0.3 parts; 3.0–8.0 parts of neutral silica sol; 2.0–5.0 parts of industrial-grade zinc phosphate powder; The cementitious material is composed of 35.0% to 45.0% silicate cement clinker and 55.0% to 65.0% granulated blast furnace slag powder, accounting for 35.0% to 45.0% of the total weight of the cementitious material. The corrosion-resistant concrete for the steel sheet piles used for the waterway revetment is prepared through the following steps: In a twin-shaft concrete mixer, the coarse aggregate, the fine aggregate, the silicate cement clinker and the granulated blast furnace slag powder are added and dry-mixed to obtain a dry-mixed mixture. The pre-prepared composite anti-corrosion dispersion is added to the twin-shaft concrete mixer and forcibly mixed with the dry mixture to obtain anti-corrosion concrete slurry. The anti-corrosion concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles, and the anti-corrosion concrete slurry forms a boundary slurry-rich transition zone on the surface of the hot-rolled U-shaped steel sheet piles. A high-frequency vibrator is inserted into the anti-corrosion concrete slurry inside the cast-in-place beam formwork. The high-frequency vibrator is turned on to vibrate the concrete, and the mechanical vibration generated by the high-frequency vibrator causes the boundary slurry-rich transition zone to undergo shear thinning. After the vibration is completed, the high-frequency vibrator is pulled out to promote the static hydration reaction of the anti-corrosion concrete slurry. After the static hydration is completed and the slurry hardens and solidifies, the anti-corrosion concrete of the waterway revetment steel sheet pile is obtained. The high-frequency vibrating rod is inserted at a normal distance of 10-15 cm from the surface of the hot-rolled U-shaped steel sheet pile, in a direction parallel to the hot-rolled U-shaped steel sheet pile.
2. The anti-corrosion concrete for waterway revetment using sheet piles according to claim 1, characterized in that, The artificially synthesized lithium magnesium silicate nanosheets have a single sheet diameter of 25–30 nm and a thickness of 0.8–1.2 nm; The neutral silica sol has an average particle size of 10–20 nm, and the industrial-grade zinc phosphate powder has a median particle size of 2.0–5.0 μm. The partially hydrolyzed polyvinyl alcohol has a degree of hydrolysis of 87.0% to 89.0% and an average degree of polymerization of 1700 to 1800. The sodium alginate powder was prepared into a 1% sodium alginate aqueous solution with a viscosity of 200-300 mPa·s at 20°C.
3. The anti-corrosion concrete for waterway revetment using sheet piles according to claim 1, characterized in that, The fine aggregate is medium-coarse river sand, and the coarse aggregate is continuously graded crushed stone with a particle size of 5.0 to 25.0 mm.
4. A method for preparing anti-corrosion concrete using steel sheet piles for waterway revetment, characterized in that, The method for preparing the anti-corrosion concrete for waterway revetment steel sheet piles as described in any one of claims 1-3 includes the following steps: In a twin-shaft concrete mixer, coarse aggregate, fine aggregate, silicate cement clinker and granulated blast furnace slag powder are added and dry-mixed to obtain a dry-mixed mixture. The pre-prepared composite anti-corrosion dispersion is added to the twin-shaft concrete mixer and forcibly mixed with the dry mixture to obtain anti-corrosion concrete slurry. The anti-corrosion concrete slurry is poured into the cast-in-place tie beam formwork containing hot-rolled U-shaped steel sheet piles, and the anti-corrosion concrete slurry forms a boundary slurry-rich transition zone on the surface of the hot-rolled U-shaped steel sheet piles. A high-frequency vibrator is inserted into the anti-corrosion concrete slurry inside the cast-in-place beam formwork. The high-frequency vibrator is turned on to vibrate the concrete, and the mechanical vibration generated by the high-frequency vibrator causes the boundary slurry-rich transition zone to undergo shear thinning. After the vibration is completed, the high-frequency vibrator is pulled out, which promotes the anti-corrosion concrete slurry to undergo a static hydration reaction. After the static hydration is completed and the slurry hardens, the anti-corrosion concrete of the waterway revetment steel sheet pile is obtained.
5. The preparation method according to claim 4, characterized in that, The input consists of sequentially adding the coarse aggregate, the fine aggregate, the silicate cement clinker, and the granulated blast furnace slag powder. The dry mixing process involves turning on the twin-shaft concrete mixer and mixing the concrete until it is homogeneous, with the dry mixing time being 15 to 20 seconds.
6. The preparation method according to claim 4, characterized in that, While keeping the twin-shaft concrete mixer running, the composite anti-corrosion dispersion is pumped into the twin-shaft concrete mixer in one go using a fluid pump for addition. The forced mixing time is 90-120 seconds, and the material is discharged after forced mixing.
7. The preparation method according to claim 4, characterized in that, The anti-corrosion concrete grout forms the boundary grout-rich transition zone within a range of 0-5mm from the surface of the hot-rolled U-shaped steel sheet pile. The vibration process involves setting the vibration frequency of the high-frequency vibrator to 150-200Hz and continuously vibrating a single point for 30-50 seconds.
8. The preparation method according to claim 4, characterized in that, The operation of pulling out the high-frequency vibrating rod is to pull it out slowly and uniformly at a speed of 0.1 to 0.2 m / s; The static hydration reaction of the anti-corrosion concrete slurry is carried out under conditions without mechanical interference.
9. The preparation method according to claim 4, characterized in that, The preparation process of the pre-prepared composite anti-corrosion dispersion includes a preliminary stage for preparing an intermediate mixture, specifically including: Inject industrial tap water into a sealed dispersion vessel equipped with a high-shear disperser, a jacketed temperature control device, and a condenser reflux device. Adjust the water temperature to 35-45°C, turn on the stirrer, and slowly sieve in artificially synthesized lithium magnesium silicate nanosheets while stirring at a low speed of 500-800 rpm. After the feeding is completed, the stirring speed is increased to 2000-2500 rpm, and high shear dispersion is carried out continuously for 30-45 minutes to promote the uniform dispersion of the artificially synthesized lithium magnesium silicate nanosheets and obtain a primary dispersion. A heat-conducting medium is introduced into the jacket of the sealed dispersion vessel to raise the temperature of the primary dispersion liquid in the sealed dispersion vessel to 80-85°C. The speed of the stirrer is reduced to 500-800 rpm, and some alcoholysis-type polyvinyl alcohol and sodium alginate powder are slowly added. Maintain a constant temperature and stir continuously for 45–60 minutes until the partially hydrolyzed polyvinyl alcohol and the sodium alginate powder dissolve to obtain an intermediate mixture.
10. The preparation method according to claim 9, characterized in that, The preparation process of the composite anticorrosive dispersion also includes a stage in which the intermediate mixture is used to finally obtain the composite anticorrosive dispersion, specifically including: Cooling water is introduced into the jacket of the sealed dispersion vessel to cool the intermediate mixture in the sealed dispersion vessel to 55-60°C. Sodium tetraborate decahydrate and sodium gluconate are added to the sealed dispersion vessel. The speed of the stirrer is reduced to 300-500 rpm, and the reaction is carried out at a constant temperature for 20-30 minutes to obtain a crosslinked mixture. The cross-linked mixture in the sealed dispersion vessel is further cooled to 35-40°C, and neutral silica sol is added dropwise at a uniform rate. The mixture is then mixed for 10-15 minutes to obtain a silica-containing mixture. The industrial-grade zinc phosphate powder is added to the silicon-containing mixture, and the stirring speed is increased to 1000-1500 rpm. The mixture is continuously dispersed for 20-30 minutes to promote the mixing of the silicon-containing mixture and the industrial-grade zinc phosphate powder into a uniformly suspended composite anti-corrosion dispersion, which is then discharged for later use.
Citation Information
Patent Citations
Anti-corrosion, anti-rust, anti-seepage and anti-crack concrete prepared from nanometer materials
CN121318256A
Anti-corrosion marine concrete and preparation method thereof
CN121948891A